Optimization of InGaAsSb Thermophotovoltaic Cell for Waste Heat Harvesting Application - Rosli R.; Lee H.J.; Jamaludin M.Z.; Gamel M.M.A.; Ker P.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Conversion efficiency; Cytology; Energy efficiency; Fossil fuels; Gallium alloys; III-V semiconductors; Indium alloys; Semiconductor alloys; Waste heat utilization; Blackbody temperatures; Energy conversion efficiency; Energy demands; Heat harvesting; Narrow bandgap; Optimisations; Performance; Thermophotovoltaics; Thermophotovoltaics cells; Waste heat harvesting; Waste heat